SMART PAIRING PROTOCOL FOR WEARABLE DEVICES BASED ON SYMMETRIC-KEY AUTHENTICATED KEY-EXCHANGE (SAKE) - Putri Utami, Mayangsari
The problem with wearable devices is that they provide secure communication. In addition, it poses new challenges to the solution to authenticate various heterogeneous IoT devices to their respective trust domains. User pairing protocol is a mechanism used to provide secure communication on wearable devices. Using a predefined password or key has a weakness that limits its use. Required key exchange protocols in asymmetric key settings are known to provide stronger security properties than protocols in key-symmetric cryptography. In particular, the protocol can provide perfect forward secrecy, as illustrated by the key exchange protocol based on the Diffie-Hellman scheme. But the public key algorithm is too heavy for low resource devices which then cannot benefit from advanced secrecy. In this study, smart pairing protocols for wearable devices were designed using the symmetric-key authentication key exchange (SAKE) protocol. The formal protocol security analysis uses the use of scyther tools and discusses its informal security analysis to show that the protocol is resistant to known attacks and specifically fixes the forward secrecy problem that occurs in Diffie-Hellman. The protocol designed shows better performance than related research in terms of security features. The key exchange protocol is authenticated in a symmetrical key arrangement that ensures complete forwarding confidentiality.